A preliminary framework of measuring music attractiveness based on facial beauty theory - Hoo, Yong Leng; Mohd Norowi, Noris; Jantan, Azrul Hazri (IEEE, 2016)
Music is a performing art that put varieties of sound together to form a sequence of sound that people will find it interesting. In past, only those with certain level of musical knowledge were able to compose music as it is very time consuming to learn and practice musical instruments. Since the advent of modern computing, various methods were introduced to help music composition, such as Markov Chain (MC), Genetic Algorithm, Knowledge-Based system, and Cellular Automata. However, previous studies were paying less effort on evaluating the quality of music from human perception. The proposed system will apply a hybrid concept by combining few composition techniques to generate music with musical patterns. A framework on determining characteristics of a good music will be proposed in this paper as well.